Recent advances in strategies for overcoming hypoxia in photodynamic therapy of cancer. (1st November 2020) - Pucelik, Barbara; Sułek, Adam; Barzowska, Agata; Dąbrowski, Janusz M.
Abstract: The selectivity of photodynamic therapy (PDT) derived from the tailored accumulation of photosensitizing drug (photosensitizer; PS) in the tumor microenvironment (TME), and from local irradiation, turns it into a "magic bullet" for the treatment of resistant tumors without sparing the healthy tissue and possible adverse effects. However, locally-induced hypoxia is one of the undesirable consequences of PDT, which may contribute to the emergence of resistance and significantly reduce therapeutic outcomes. Therefore, the development of strategies using new approaches in nanotechnology and molecular biology can offer an increased opportunity to eliminate the disadvantages of hypoxia. Emerging evidence indicates that wisely designed phototherapeutic procedures, including: (i) ROS-tunable photosensitizers, (ii) organelle targeting, (iii) nano-based photoactive drugs and/or PS delivery nanosystems, as well as (iv) combining them with other strategies ( i.e. PTT, chemotherapy, theranostics or the design of dual anticancer drug and photosensitizers) can significantly improve the PDT efficacy and overcome the resistance. This mini-review addresses the role of hypoxia and hypoxia-related molecular mechanisms of the HIF-1α pathway in the regulation of PDT efficacy. It also discusses the most recent achievements as well as future perspectives and potential challenges of PDT application against hypoxic tumors.